Synthesis of double perovskite and quadruple perovskite nanocrystals through post-synthetic transformation reactions. Issue 17 (8th April 2022) - Yang, Hanjun; Cai, Tong; Dube, Lacie; Chen, Ou
Abstract : Lead-free perovskite nanocrystals are synthesized by post-synthetic transformation reactions. The post-synthetic transformations show the structural flexibility of zero-dimensional perovskite nanocrystal materials. Abstract : Lead-free halide perovskite nanocrystals (NCs) represent a group of emerging materials which hold promise for various optical and optoelectronic applications. Exploring facile synthetic methods for such materials has been of great interest to not only fundamental research but also technological implementations. Herein, we report a fundamentally new method to access lead-free Bi-based double perovskite (DP) and quadruple perovskite (or layered double perovskite, LDP) NCs based on a post-synthetic transformation reaction of Cs3 BiX6 (X = Cl, Br) zero-dimensional (0D) perovskite NCs under mild conditions. The produced NCs show good particle uniformity, high crystallinity, and comparable optical properties to the directly synthesized NCs. The relatively slow kinetics and stop-on-demand feature of the transformation reaction allow real-time composition–structure–property investigations of the reaction, thus elucidating a cation-alloyed intermediate-assisted transformation mechanism. Our study presented here demonstrates for the first time that post-synthetic transformation of 0D perovskite NCs can serve as a new route towards the synthesis of high-quality lead-free perovskite NCs, and provides valuable insights into the crystal structures, excitonic properties and their relationships of perovskite NCs.